2023
DOI: 10.1038/s41419-023-06005-6
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis in renal inflammation and fibrosis: current knowledge and clinical significance

Abstract: Pyroptosis is a novel inflammatory form of regulated cell death (RCD), characterized by cell swelling, membrane rupture, and pro-inflammatory effects. It is recognized as a potent inflammatory response required for maintaining organismal homeostasis. However, excessive and persistent pyroptosis contributes to severe inflammatory responses and accelerates the progression of numerous inflammation-related disorders. In pyroptosis, activated inflammasomes cleave gasdermins (GSDMs) and generate membrane holes, rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…Podocyte death is induced by multiple factors. Among canonical programmed cell death pathways, apoptosis stands out as the predominant type, although it occasionally intersects with others, notably necroptosis and pyroptosis 92,111,112 . Both necroptosis and pyroptosis are inflammation‐inducible pathways that feature a loss of plasma integrity and are characterized by a cascade of signals including MLKL and inflammasome activation, respectively 71 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Podocyte death is induced by multiple factors. Among canonical programmed cell death pathways, apoptosis stands out as the predominant type, although it occasionally intersects with others, notably necroptosis and pyroptosis 92,111,112 . Both necroptosis and pyroptosis are inflammation‐inducible pathways that feature a loss of plasma integrity and are characterized by a cascade of signals including MLKL and inflammasome activation, respectively 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Among canonical programmed cell death pathways, apoptosis stands out as the predominant type, although it occasionally intersects with others, notably necroptosis and pyroptosis. 92,111,112 Both necroptosis and pyroptosis are inflammation-inducible pathways that feature a loss of plasma integrity and are characterized by a cascade of signals including MLKL and inflammasome activation, respectively. 71 Additionally, in the absence of concrete evidence regarding the occurrence of ferroptosis in LN podocytes, additional findings are needed to conclusively understand podocyte dysfunction in LN.…”
Section: Targeting Podocyte Deathmentioning
confidence: 99%
“…Studies on GSDMD-deficient mice indicate heightened vulnerability to injury in both IRI and cisplatin-induced acute kidney injury (AKI) models. Conversely, other research suggests that either genetic deficiency of GSDMD or inhibition of the NLRP3 inflammasome might offer protection in AKI models [ 173 , 174 , 177 ]. Importantly, despite in vivo data post-IRI and single-cell analysis, GSDMD expression hasn’t been observed in tubular epithelial cells following murine kidney IRI [ 176 , 178 ].…”
Section: Renal Injury and Inflammasomesmentioning
confidence: 99%
“…A number of recent studies reported NMs-assisted GBS therapy for instance ferroptosis, gene therapy (GT) [ 266 , 273 ], radiotherapy [ 274 ], photothermal therapy (PTT) [ 275 ], magnetothermal therapy [ 276 , 277 ], and immunotherapy [ 278 ]. Ferroptosis is an iron-mediated apoptosis distinguished from necrosis, autophagy [ 279 ], apoptosis, and pyroptosis [ 280 ]. Excess amount of iron reacts with H 2 O 2 and generates free radicals and singlet O 2 in cells.…”
Section: Neurological Diseases Associated With Signaling Pathways Of ...mentioning
confidence: 99%